Fluoro-functionalized ionic covalent organic frameworks (F-iCOFs) for highly selective enrichment and sensitive determination of perfluorinated sulfonates by MALDI-MS - Liu, Xiao-Pan; Sun, Wen-Qian; Zhao, Meng-Ge; Zhang, Xing-Jie; Liu, Li-Hong; Chen, Chang-Po (Mikrochimica acta (1966), 2022)
An easily prepared fluoro-functionalized ionic covalent organic framework (F-iCOF) has been implemented into MALDI-TOF MS, enabling the highly selective enrichment and sensitive determination of perfluorinated sulfonate (PFS) contaminants in a rapid and convenient manner. The good thermal stability and excellent optical absorption properties of F-iCOF makes it a brilliant matrix with no background noise. Moreover, benefitting from the large surface area, appropriate pore size, good water dispersibility, and abundant fluorine atom and cationic characteristic of F-iCOF, it exhibited superior adsorption capacity and enrichment selectivity towards PFSs. Good signal responses for PFSs were obtained in the presence of various interfering compounds such as BSA, HA, or even more than 100-fold excess of glutamic acid and similar in structure sodium alkyl sulfonates, highlighting the specific selectivity of F-iCOF. Calibration curves for potassium perflurobutane sulfonate (PFBSK) in tap water and whole blood were established with good linear correlation in the range 1–500 pg mL −1 . The limits of detection and quantification for PFBSK were as low as 0.04 pg mL −1 and 0.05 pg mL −1 , respectively, which are comparable or better than the existing methods for the determination of PFSs. Graphical Abstract